A Harold Pinter Chronology - Baker, W. author. aut Link
XIX, 374 p.
Keywords: The most detailed chronological account of Harold Pinter to appear, this new volume in the Author Chronologies series traces the daily activities of the Nobel Prize winning author. It is based upon published and unpublished materials, and discussion with his close friends, and is a basic reference tool for all Pinter students and scholars.